Secondary Ion Mass Spectrometry Bias on Isotope Ratios in Dolomite–Ankerite, Part I: δ18O Matrix Effects. Issue 2 (8th August 2015) - Śliwiński, Maciej G.; Kitajima, Kouki; Kozdon, Reinhard; Spicuzza, Michael J.; Fournelle, John H.; Denny, Adam; Valley, John W.
Abstract : We document the development of a suite of carbonate mineral reference materials for calibrating SIMS determinations of δ 18 O in samples with compositions along the dolomite–ankerite solid solution series [CaMg(CO3 )2 –CaFe(CO3 )2 ]. Under routine operating conditions for the analysis of carbonates for δ 18 O with a CAMECA IMS 1280 instrument (at WiscSIMS, University of Wisconsin‐Madison), the magnitude of instrumental bias along the dolomite–ankerite series decreased exponentially by 10‰ with increasing Fe content in the dolomite structure, but appeared insensitive to minor Mn substitution [< 2.6 mol% Mn/(Ca+Mg+Fe+Mn)]. The compositional dependence of bias (i.e., the sample matrix effect) was calibrated using the Hill equation, which relates bias to the Fe# of dolomite–ankerite [i.e., molar Fe/(Mg+Fe)] for thirteen reference materials (Fe# = 0.004–0.789); for calibrations employing either 10 or 3 μm diameter spot size measurements, this yielded residual values ≤ 0.3–0.4‰ relative to CRM NBS 19 for most reference materials in the suite. Analytical precision was ± 0.3‰ (2 s, standard deviations) for 10‐μm spots and ± 0.7‰ (2 s ) for 3‐μm spots, based on the spot‐to‐spot repeatability of a drift monitor material that 'bracketed' each set of ten sample‐spot analyses. Analytical uncertainty for individual sample analyses was approximated by a combination of precision and calibration residual values (propagated in quadrature), suggesting an uncertainty of ± 0.5‰ (2 s ) for 10‐μm spots and ± 1‰ (2 s ) for 3‐μm spots. Key Points: Calibration of matrix effects (instrumental bias) in the analysis of δ 18 O by Secondary Ion Mass Spectrometry from carbonate mineral compositions of the dolomite‐ankerite solid solution. Suite of reference materials developed and documented. The matrix effect changes exponentially with increasing Fe‐content in the dolomite crystal structure (using a CAMECA IMS 1280 instrument).